Corrigendum to "Hyperfine structure of quadrupole rovibrational transitions in tritium-bearing hydrogen isotopologues" [J. Quant. Spectrosc. Radiat. Transf. 256 (2020), 107255]. (May 2021) - Jóźwiak, Hubert; Cybulski, Hubert; Wcisło, Piotr
Highlights: Corrigendum to "Hyperfine structure of quadrupole rovibrational transitions in tritium-bearing hydrogen isotopologues" [J. Quant. Spectrosc. Radiat. Transf. 256 (2020), 107255]